How is The Role of Academic Culture in Improving Lecturer Productivity in Research and Supporting Accreditation - Astrid Chandra Sari; Sukestiyarno Sukestiyarno; Agus Wahyudin; Masrukhan Masrukhan (Universitas Negeri Semarang, 2023)
One important factor that influences the quality of higher education is qualified lecturers. The management of lecturers must have the main target, namely increasing the quality of their productivity through increasing work efficiency as educators, researchers and community service or more precisely in providing services to the community. Institutional support as one of the environmental factors was found to be an important factor in research productivity. The management literature indicates that there are various factors associated with effective performance outcomes. For example, some suggest it is related to managerial practice. This study aims to provide a more in-depth study related to the relationship between Academic Culture in increasing research productivity and supporting accreditation. The approach used in this research study is to adopt a literature study approach. The results of the study obtained show that several studies have proven that Academic Culture has an effect on Lecturer Productivity in the research field. Academic culture does not just grow, or originates from applied rules and regulations, but is rooted in scientific norms and values. With the development of academic culture, it encourages lecturers to actively conduct research. The existence of a quality assurance system allows the growth of a culture of quality within the existing academic culture, so that the whole process of quality assurance in the education system in the form of setting standards, implementing standards, evaluating the implementation of standards and efforts to continuously improve the implementation of standards can become part of life in higher education.